Upaya Penyuluh Agama dalam Meningkatkan Pemahaman Pendidikan Agama Islam di Desa Pematang Buluh Kecamatan Tanjung Beringin Kabupaten Serdang Bedagai - Muhammad Mazwan; M. Syukri Azwar Lubis2; Pan Suadi (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
This study aims to discuss the efforts made to improve the understanding of Islam by religious instructors in Pematang Buluh Village. This research is a type of qualitative research. This study uses primary and secondary data sources. Data collection techniques using interviews, observations or observations and documents. The data that has been organized is then managed by reducing it, presenting the data and then drawing conclusions. To examine the validity of the data with the stages of credibility (trust), transferability (transferability), Dependability (dependence) and confirmability (certainty). Based on the results of the study, it was found that the efforts made to improve the understanding of Islam by religious instructors in Pematang Buluh Village, these efforts were carried out by civil servant religious instructors who were officially SK-kan by the Regency Ministry of Religion and non-civil servant religious instructors or those in the community and appointed by the community itself and efforts to increase understanding of Islam carried out by religious instructors in Pematang Buluh Village are religious counseling in the field of faith, counseling in the field of sharia, in the field of worship and personal and public issues related to religion. The obstacles faced to improve the understanding of Islam by religious instructors in Pematang Buluh Village are basically the problem of the presence of the community in participating in the religious counseling carried out, because in general the people of Pematang Buluh Village, especially the men, work at sea and sometimes go home for two days. once even once a week.